Foundation Version Control for Web Developers - Kemper, Chris; Oxley, Ian.; SpringerLink (Online service) (Berkeley, CA : Apress, 2012)
Foundation Version Control for Web Developers explains how version control works, what you can do with it and how. Using a friendly and accessible tone, you will learn how to use the three leading version control systems$1 (BSubversion, Git and Mercurial$1 (Bon multiple operating systems. The history and integral concepts of version control are covered so that you will gain a thorough understanding of the subject, and why it should be used to manage all changes in web development projects. This book covers the valuable knowledge and transferable skills that will enable you use one of the three leading systems as well as easily switch to new systems that will arise in the workplace. Topics covered include: How to choose the correct software for your needs. Creating and working with repositories. Understanding trunks, branches, hooks, conflicts and merging. Setting up respository servers and integrating with Apache. Using Terminal, and understanding alternatives. Foundation Version Control for Web Developers is a concise beginner$1 (Bs course for designer and developer alike. Even if you have no prior knowledge of version control, this book will provide you with the knowledge to fully manage projects from start to finish, ensuring your projects are as seamless and successful as you need them to be.s
Keywords: Computer science; Computer Science; Computer Science, general